Impact De La Volatilité De Change Sur La Performance Financière Des Entreprises Cotées - Mrhari, El Mehdi; Daoui, Driss (European Scientific Journal, ESJ, 2018)
The main objective of this article is to measure and analyze the exchange rate volatility impact on the financial performance of Moroccan companies listed on Casablanca Stock Exchange during the last decade. We used linear models to study a sample of 56 companies. This paper prove the link between Dirham volatility and the companies financial performance, however this relationship was weak. In addition, we discussed the causes of this phenomenon and its managerial implications.